Integrated acupuncture-pharmacotherapy for perimenopausal insomnia: a systematic review and meta-analysis - Yang, Boxiang; Jiang, Shengwen; Teng, Yubo; Wang, Yiming; Zhang, Jingyi; Gao, Chang; Song, Chunhua (Frontiers in Neurology, 2025)
ObjectiveInsomnia is a prevalent symptom among perimenopausal women, mainly attributed to estrogen-progesterone imbalance and neuropsychiatric factors, significantly impacting their quality of life. This article seeks to systematically evaluate the efficacy of integrated acupuncture-pharmacotherapy (AP) in treating perimenopausal insomnia (PMI), offering new insights for the management of insomnia in women.MethodsSearches were conducted in 8 databases: PubMed, Web of Science (WOS), Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), China Biology Medicine Disc (CBM), Wanfang Academic Journal Full-text Database (Wanfang), and Chongqing VIP Database (CQVIP). Database searches extended through August 1, 2024. Endnote 20 was used to build the database and screen for eligible randomized controlled trials (RCTs). The efficacy of AP for PMI were demonstrated by assessing 3 primary outcome measures (Effective rate, Hamilton Anxiety Scale [HAMA], Traditional Chinese Medicine Syndromes [TCMS]) and 5 secondary outcome measures (Pittsburgh Sleep Quality Index [PSQI], Modified Kupperman Index [KMI], Luteinizing Hormone [LH], Follicle-Stimulating Hormone [FSH], Estradiol [E2]). The risk of bias was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions. Data analysis was performed using RevMan 5.4 and StataMP 15.0. Subgroup or sensitivity analysis was applied as necessary to address issues of heterogeneity. Regression analysis was used to determine whether the division of potential subgroups is reasonable. The evidence quality level was evaluated using the GRADEprofiler following the GRADE approach.ResultsA total of 12 eligible studies comprising 969 PMI cases were ultimately included in this meta-analysis. Pooled results indicated AP had statistically significant benefits for PMI: Efficacy (Effective rate [RR = 1.22, 95% CI (1.13, 1.30), Z = 3.88, p < 0.00001]), Scores (HAMA [MD = −3.26, 95% CI (−3.79, −2.73), Z = 12.06, p < 0.00001]), TCMS [MD = −0.98, 95% CI (−1.21, −0.74), Z = 7.99, p < 0.00001], PSQI [MD = −3.12, 95% CI (−4.21, −2.03), Z = 5.63, p < 0.00001], KMI [MD = −3.96, 95% CI (−5.78, −2.15), Z = 4.28, p < 0.0001], and Hormone levels LH [MD = −10.16, 95% CI (−16.41, −3.91), Z = 3.18, p = 0.001 < 0.05], FSH [MD = −8.65, 95% CI (−13.67, −3.64), Z = 3.39, p = 0.0007 < 0.05], E2 [MD = 15.87, 95% CI (10.16, 21.58), Z = 5.45, p < 0.00001].ConclusionAP demonstrates significant efficacy in treating PMI patients, offering an innovative integrative therapy with substantial clinical value. Future studies should involve more large-scale, multicenter RCTs with long-term follow-up.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024579691.